Computer Vision Syndrome among Call Center Employees at Telecommunication Company in Bandung - Nursyifa, Ghea; Santoso, Putri Teesa Radhiyanti; Musa, Ine Renata (Althea Medical Journal, 2016)
Background: The occurrence of Computer Vision Syndrome (CVS) at the workplace has increased withinÂ decades due to theprolonged use of computers. Knowledge of CVS is necessary in order to develop anÂ awareness of how to prevent and alleviate itsprevalence . The objective of this study was to assess theÂ knowledge of CVS among call center employees and to explore the most frequent CVS symptom experiencedÂ by the workers.Methods: A descriptive cross sectional study was conducted during the period of September to NovemberÂ 2014 at Telecommunication Company in Bandung using a questionnaire consisting of 30 questions. Out ofÂ the 30 questions/statements, 15 statements were about knowledge of CVS and other 15 questions wereÂ about the occurrence of CVS and its symptoms. In this study 125 call center employees participated asÂ respondents using consecutive sampling. The level of knowledge was divided into 3 categories: good (76â100%), fair (75â56%) and poor (<56%). The collected data was presented in frequency tabulation.Results: There was 74.4% of the respondents had poor knowledge of CVS. The most symptom experiencedÂ by the respondents was asthenopia.Conclusions: The CVS occurs in call center employees with various symptoms and signs. This situationÂ is not supported by good knowledge of the syndrome which can hamper prevention programs.Â [AMJ.2016;3(2):181â21]DOI:Â 10.15850/amj.v3n2.789